Similarity Solutions for Unsteady Hydromagnetic Free Convection Boundary Layer Flow over Flat Plates with Thermophoresis (Journal of Scientific Research, 2016)
This paper is focused on the analysis of thermophoresis on an unsteady two dimensional free convective boundary layer flow along a permeable inclined flat plate in the presence of magnetic field and thermophoresis. Governing time dependent partial differential equations are non- dimensionalzed and transformed into a system of nonlinear ordinary differential equations by applying similarity transformations. These are solved numerically by using the shooting method along with Runge-Kutta sixth order integration scheme. Numerical results for the dimensionless velocity, temperature and concentration profiles have been obtained and displayed graphically. The skin-friction coefficient, wall heat transfer coefficient and wall deposition flux rate have also been obtained and are presented in tabular form. The obtained numerical results also show that increased unsteadiness parameter significantly controls the thermophoretic particle.